2014
DOI: 10.3855/jidc.3978
|View full text |Cite
|
Sign up to set email alerts
|

Differential replication of dengue virus serotypes 2 and 3 in coinfections of C6/36 cells and Aedes aegypti mosquitoes

Abstract: Introduction: Different dengue virus (DENV) serotypes have been associated with greater epidemic potential. In turn, the increased frequency in cases of severe forms of dengue has been associated with the cocirculation of several serotypes. Because Colombia is a country with an endemic presence of all four DENV serotypes, the aim of this study was to evaluate the in vivo and in vitro replication of the DENV-2 and DENV-3 strains under individual infection and coinfection conditions. Methodology: C6/36HT cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…These primers amplify a 119 bp segment of the C-prM region of the viral genome. Amplification was performed in a Bio-Rad CFX96TM Real-Time System C 1000 Thermal Cycler, and the genomic copies were calculated using a specific standard curve for DENV-2 that was constructed previously [34]. The results are expressed as the mean of four independent experiments ( n  = 4).…”
Section: Methodsmentioning
confidence: 99%
“…These primers amplify a 119 bp segment of the C-prM region of the viral genome. Amplification was performed in a Bio-Rad CFX96TM Real-Time System C 1000 Thermal Cycler, and the genomic copies were calculated using a specific standard curve for DENV-2 that was constructed previously [34]. The results are expressed as the mean of four independent experiments ( n  = 4).…”
Section: Methodsmentioning
confidence: 99%
“…Six studies examined the infectivity of different dengue viral strains, and the impact of co-infection [148,172,197200]. Quintero-Gil et al [198] found that the DENV-2 serotype performed with a thousand-fold greater efficiency than the DENV-3 serotype, upon co-infection. Vazeille et al [200] found that DENV-4 outperformed DENV-1 in Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies examined natural infection rates of Zika virus [129,130], vertical transmission [179], or co-infection with other viruses [126]. This is in contrast to the wealth of research available on natural infection and co-infection for dengue and chikungunya viruses, although vertical transmission research was sparse for all three viruses [144,148,156,175,178,197,198]. Based on the internationally recognized urgency of Zika virus infection as a public health concern, and potential increase in the importance of this and other emerging arboviruses in the future, further research on arbovirus vectors and transmission dynamics is of pressing need.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, entomologic studies suggest that coinfecting arboviruses may compete within vectors, an effect known as superinfection exclusion . This phenomenon was shown between different dengue serotypes and between dengue and yellow fever viruses although not yet demonstrated for superinfections with ZIKV and other arbovirus …”
Section: Recent Trends: Lower Microcephaly Rates In the 2016 Outbreakmentioning
confidence: 99%